Clinical and manometric postoperative evaluation of posterior sagital anorectoplasty (PSARP) in patients with upper and intermediate anorectal malformations - Martins, José Luiz; Pinus, José (São Paulo Medical Journal, 1996)
PSARP is currently the most widely-used surgical technique for surgical correction of high and intermediary anorectal malformations, but there is much controversy in the literature about the postoperative evaluation of these cases. We studied 27 cases of anorectal malformations operated with PSARP from clinical and manometric aspects in order to analyze: 1) fecal continence; 2) the relationship between fecal continence and the associated sacral anomalies and; 3) the relationship between the postoperative manometric evaluation and fecal continence. From the analysis of 27 cases of high and intermediary anorectal malformations, we concluded that: 1) fecal continence was achieved in 48.14 percent of the cases; partial fecal continence in 25.92 percent; and fecal incontinence in 25.92 percent of the cases; 2) the presence of fecal incontinence was directly related to the association of sacral anomalies and; 3) anorectal manometry is a useful test to evaluate the patients operated by PSARP, due to the existence of a relationship between the manometric results and the degree of fecal continence.